FORMATION FEATURES OF PUBLIC OPINION AND DEVELOPMENT STAGES - AVETISYAN, ASTGHIK (Main Issues Of Pedagogy And Psychology, 2015)
The public opinion reflects a true picture of public consciousness, public interests, moods and feelings of various social groups. The main methods of public opinion formation are suggestion, infection, persuasion and imitation. The main instruments of opinion formation are mass media, oral propaganda, political agitation and interpersonal communication. Development of public opinion passes various stages: formation, functioning, expression and realization in practice. It can be formed spontaneously and consciously. The analysis of scientific literature shows that researchers have some approaches to allocation ofstages. Key words: public opinion, mass media, public consciousness, study methods, document analysis, opinion poll, stereotypes, image, advertisement, spiral of silence, impact, collective consciousness.